Konforme Abbildung von symmetrischen Halbstreifen und Eckengebielen - Goldberg, A.; Strotschik, T. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Гольдберг, Т. В. Строчик. Конформное отображение симметричных полуполос и угловых областейA. Goldbergas, T. Stročik, Simetriškų pusjuosčių ir kampuotų sričių konformiškas vaizdavimas